KONDISI FISIK RUMAH DAN PERILAKU MASYARAKAT TERHADAP KEBERADAAN VEKTOR TIKUS DI KELURAHAN KAMPUNG BARU KECAMATAN SENAPELAN KOTA PEKANBARU TAHUN 2017 - nila puspita sari; Tira Septia Paleri (Jurnal Kesehatan Komunitas, 2020)
Poor Sanitaon, trash management, and the blockage of waterways was a cause of the high populaon of rodents. Rodent were known as vector of infecon diseases such Leptospirosis and Salmonellosis and it very important to protect housing sanitaon in Pekanbaru, especially Kampung Baru. This study aims to determine the relaonship between the physical condion of the house and the behavior of the community to the existence of rat vector in Kampung Baru village, Senapelan sub-district, Pekanbaru City. This study was a quantave analyc with crossseconal design. Populaon was house of cizen in Kampung Baru Sub-District of Senapelan Sub-Province Pekanbaru City. There were 67 households as samples in RW 06 Region. The results showed that there were correlaons on wall variables (p = 0.002), ceiling (p = 0.048), venlaon (p = 0.026), and SPAL (p = 0.020). There was no correlaon on the variable of the goodslayout (p = 0,060), and waste management (p = 0,437) The layout of respondent goods smoothed every 1-2 weeks and daily garbage management always take the household waste and dispose of directly to the disposal place the end of the far away from their community. We recommend that people should pay more aenon to cleanliness in the environment where they lived to avoid the rodent vector that can enter their home. Keywords : Physical House, Community Behavior, Rodent